Peningkatan Kebersihan Gigi dan Mulut pada Lansia: Identifikasi dan Intervensi Faktor Pendukung di Komunitas - Aisyah AR; Rumaisha Soumena; Dewi Sartika; Dwi Rezky Aulyah; Arfiah Jauharuddin (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2024)
Oral health is an important aspect in maintaining the quality of life of the elderly. However, the elderly often face challenges in maintaining oral hygiene due to decreased physical abilities, changes in cognitive status, and lack of knowledge and access to dental health services. This study aims to identify factors that influence oral hygiene in the elderly and to develop an effective community-based intervention to improve oral hygiene among the elderly. The methods used in this study included a survey of knowledge, attitudes, and oral hygiene practices before and after counseling, as well as direct observation of oral hygiene in 50 elderly in the local community. The intervention was carried out through counseling, training, and providing support from family and community. The results showed a significant increase in knowledge of the elderly, from 60% before counseling to 85% after. Positive attitudes also increased, with more than 80% of the elderly showing a stronger intention to maintain oral hygiene independently. Oral hygiene practices also improved, with 75% of participants reporting brushing their teeth at least twice a day after the intervention, compared to 40% before the intervention. In addition, family and community support play an important role in facilitating these behavioral changes. The conclusion of this study is that a comprehensive community-based intervention is effective in improving oral hygiene in the elderly. This approach, which combines education, attitude change, and social support, can be a model adopted in oral health programs in other communities to improve the quality of life of the elderly.